A vida como ela é... (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
Show by the Teatro Sim Company... Why Not?!!! in 2010, at Teatro Álvaro de Carvalho - Florianópolis, SC.
Keywords: theatrical production; Nelson Rodrigues; Teatro Sim...Por Que Não?!!!